Gut Microbiota - Brain Axis 2018
DOI: 10.5772/intechopen.79863
|View full text |Cite
|
Sign up to set email alerts
|

Autism in Children Connected with Gastrointestinal Symptoms

Abstract: Autism in children has increased significantly over the last few years. Eating disorders and ailments of the gastrointestinal system are a common affliction among these children. The hypothesis linking the autism spectrum disorder (ASD) and the digestive system with its bacterial microflora based on the concept of the gut-brain axis become very interesting and credible. This axis is a two-way communication between the central nervous system (CNS) and gut innervation. Mechanisms of this dependency include effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…In conducting this study, we noted that we were the first study to include diet as a variable together with abdominal pain and stool status as potential clinical indicators of gut microbiome status. Study findings contribute to the growing literature signaling the need to more deeply understand occurrence of GI symptomatology in children with ASD (e.g., [ 55 , 56 , 57 ]), and to understand GI symptomatology in consideration of diet status and its implications in the children’s everyday lives, behaviors, and symptom severity, which in turn impacts parent and family functioning.…”
Section: Discussionmentioning
confidence: 72%
“…In conducting this study, we noted that we were the first study to include diet as a variable together with abdominal pain and stool status as potential clinical indicators of gut microbiome status. Study findings contribute to the growing literature signaling the need to more deeply understand occurrence of GI symptomatology in children with ASD (e.g., [ 55 , 56 , 57 ]), and to understand GI symptomatology in consideration of diet status and its implications in the children’s everyday lives, behaviors, and symptom severity, which in turn impacts parent and family functioning.…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, children with autism spectrum disorders are more prone to gastrointestinal (GI) disorders than the general population which can significantly impact their health, learning, and development [13]. Since gastrointestinal disorders may affect the incidence and severity of other symptoms in children with ASD, adequate nutrition is essential and can improve their life comfort and overall health [14]. Various studies suggested that the gluten-free diet may be effective in controlling gastrointestinal issues in children with ASD and improving their behaviour [15].…”
Section: Introductionmentioning
confidence: 99%